Pengaruh Kepemilikan Institusional, Intensitas Aset Tetap, Dan Financial Distress Terhadap Agresivitas Pajak - Romadhina, Anggun Putri (Universitas Gorontalo, 2023)
This research aims to provide empirical evidence of the influence of institutional ownership, fixed asset intensity, and financial distress on tax aggressiveness. The study adopts a quantitative approach and utilizes secondary data, specifically financial reports of manufacturing companies listed on the Indonesia Stock Exchange. The test results showed that institutional ownership, fixed asset intensity and financial distress simultaneously affect the aggressiveness of the tax. It can be assumed that if a company has institutional ownership, fixed asset intensity and is experiencing financial difficulties, it can affect management or company activities to take aggressive tax avoidance actions.